In Quest of Wisdom; Missing Segment of Current Medicine - Abbasi, Mahmoud (مجله اخلاق پزشکی - علمی پژوهشی, 2016)
Search for the cup of Jamshid from me, years my heart made. And for what it possessed, from a stranger, entreaty made. A jewel that is beyond the shell of existence and of time, From those lost on the shore of the sea, search it made. Last night, I took my difficulty to the Pir of the Magians. Who, by strengthening of sight, the solving of sublety made. Him, happy, laughing, wine-goblet in hand, I saw: And in the mirror, a hundred kinds of views he made. I said: ‘When gave the All-wise this cup world-viewing to thee?” He said: ‘On that day, when the azure dome He made.” Unknowingly, He was with me everywhere. I couldn’t see and my soul seekest Him, made. His magic that He all made here, Sameri had the cane but the white hands of Moses, seekest made. He said: “That friend, by whom lofty became the head of the gibbet. “His crime was this that clear, the mysteries of the sky, hemade.”If, again, the bounty of the Holy Spirit gives aid, others also may make those, which the Jesus made. I said to him: “the chain-like tress of idols is for the sake of what’?” He said: “Of his own distraught heart. Hafez complaint made.”